2018
DOI: 10.1038/s41598-018-22229-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive renoprotective effects of ipragliflozin on early diabetic nephropathy in mice

Abstract: Clinical and experimental studies have shown that sodium glucose co-transporter 2 inhibitors (SGLT2i) contribute to the prevention of diabetic kidney disease progression. In order to clarify its pharmacological effects on the molecular mechanisms underlying the development of diabetic kidney disease, we administered different doses of the SGLT2i, ipragliflozin, to type 2 diabetic mice. A high-dose ipragliflozin treatment for 8 weeks lowered blood glucose levels and reduced urinary albumin excretion. High- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 45 publications
5
55
1
Order By: Relevance
“…Furthermore, Kamezaki et al recently reported that even low-dose ipragliflozin, given to type 2 diabetic mice, reduced renal cortical hypoxia and abnormal hemodynamics in early diabetic nephropathy. In addition to these effects, high-dose ipragliflozin exerted renoprotective effects by reducing oxidative stress in tubular epithelia and glomerular podocytes [ 20 ]. These prior studies demonstrated that SGLT2 inhibitors exert renoprotective effects by having beneficial effects not only on glycemic control, glomerular hyperfiltration, blood pressure, and body weight reduction, but also through multifactorial mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kamezaki et al recently reported that even low-dose ipragliflozin, given to type 2 diabetic mice, reduced renal cortical hypoxia and abnormal hemodynamics in early diabetic nephropathy. In addition to these effects, high-dose ipragliflozin exerted renoprotective effects by reducing oxidative stress in tubular epithelia and glomerular podocytes [ 20 ]. These prior studies demonstrated that SGLT2 inhibitors exert renoprotective effects by having beneficial effects not only on glycemic control, glomerular hyperfiltration, blood pressure, and body weight reduction, but also through multifactorial mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of sodium–glucose cotransporter 2 (SGLT‐2) promote urinary glucose excretion by selectively blocking SGLT‐2 activity in proximal tubules of the kidney. SGLT‐2 inhibitors thus ameliorate hyperglycemia, dyslipidemia and insulin resistance; reduce bodyweight; and attenuate β‐cell exhaustion. However, several clinical trials have shown that the effect of these agents on bodyweight is smaller than would be expected from the increase in urinary glucose excretion.…”
Section: Introductionmentioning
confidence: 99%
“…Kidokoro et al 29 also reported that empagliflozin increased urinary adenosine excretion and reduced hyperfiltration through afferent arteriolar constriction, effects that were abolished by A1 adenosine receptor blockade in mice. In addition, ipragliflozin has been reported to suppress renal and glomerular hypertrophy, and reduce nicotinamide adenine dinucleotide phosphate oxidase 4 expression and subsequent oxidative stress in mice 30 . The fact that eGFR levels were maintained without decreasing in the eGFR <60 group in the present study suggests that this renoprotective effect confirmed in animal experiments might also occur in humans.…”
Section: Discussionmentioning
confidence: 99%